New Components for Dye-Sensitized Solar Cells. (9th May 2010) - Caramori, Stefano; Cristino, Vito; Boaretto, Rita; Argazzi, Roberto; Bignozzi, Carlo Alberto; Di Carlo, Aldo
Abstract : Dye-Sensitized Solar Cells (DSSCs) are among the most promising solar energy conversion devices of new generation, since coupling ease of fabrication and low cost offer the possibility of building integration in photovoltaic windows and facades. Although in their earliest configuration these systems are close to commercialization, fundamental studies are still required for developing new molecules and materials with more desirable properties as well as improving our understanding of the fundamental processes at the basis of the functioning of photoactive heterogeneous interfaces. In this contribution, some recent advances, made in the effort of improving DSSC devices by finding alternative materials and configurations, are reviewed.